APPLICATION CLASSIFICATION OF HANDPHONE SPECIFICATION SONY ERICSSON GSM USING VISUAL BASIC 6.0 - Agung Permana (Jurnal Sistem Informasi, 2007)
The use of application specific besifat analyze a phone with a display picture from yourmobile phone itself and accompanied by information - information such as specificationsand a brief review of the phone, then the author tries to make application of theclassification specifications sony ericsson mobile phone using Microsoft Visual Basic6.0. With this application is expected to be more varied consumers in choosing what typeof mobile suit their personalities and can also freely choose mobile phone or a budgetbased on funds that they had at the time. From the results of this study can be concludedthat by using a computerized will be easier and faster in finding information.References: 12 (1985 - 2007)Keywords: Applications, Specifications, Sony Ericsson